Trichloroacetic Acid for localized juvenile spongiotic gingival hyperplasia: a case report with a novel treatment - Moine, Lorena (2018)
Fil: Moine, Lorena. Universidad Nacional de Córdoba. Facultad de Odontología. Cátedra de Medicina Oral; Argentina.